The mental health benefits of religion and spirituality in people living with bipolar disorder in Malaysia - Mohamad Shariff, Nurasikin; Wright, Nicola; Crawford, Paul (Faculty of Medicine and Health Sciences, 2022)
Introduction: The taxonomy of spirituality is fraught with complexities concerning mental health studies, due to contextual variables such as religion. While many studies on spirituality have reported positive mental health outcomes, little is known concerning spirituality’s effects on bipolar disorder. This study aims to provide a contextual understanding of spirituality from the religious worldview of people with bipolar disorder. Method: This is a qualitative study involving semi-structured and one-to-one in-depth interviews. 25 participants diagnosed with bipolar disorder were recruited from two psychiatric outpatient clinics. All interviews were audio-taped and transcribed verbatim by the researcher. Thematic analysis is used to analyse the data and Bourdieu’s concept of habitus is used to explore the findings in relation to participants’ subjective account of their religious form of spirituality. Results: The theme ‘Maintaining a positive sense of self’ mainly comprises the religious element in the participants’ everyday life: faith in God, religious practices and a sense of spiritual harmony (i.e. peacefulness and connectedness). The role of religion and social agency was inclusive in promoting spirituality among the study sample Conclusion: Through Bourdieu’s lens of religious habitus, this study provides the understanding of religious-spirituality and a healthy mental state in such a way that it implies a relationship with God through religious beliefs and practices. This study invites others to pay attention to the dynamic roles of religious agency and society in promoting religious faith and practices among individuals diagnosed with bipolar disorder. Malaysian Journal of Medicine and Health Sciences (2022) 18(19) 55-59. doi:10.47836/mjmhs.18.s19.9